Loss of CD4 T lymphocytes in patients infected with human immunodeficiency virus type 1 is more pronounced in the duodenal mucosa than in the peripheral blood. Berlin Diarrhea/Wasting Syndrome Study Group. Issue 4 (October 1995) - Schneider, T; Jahn, H U; Schmidt, W; Riecken, E O; Zeitz, M; Ullrich, R
Abstract : Although changes in T lymphocyte subset distribution in the peripheral blood of patients infected with human immunodeficiency virus (HIV) are well defined it is not known whether these changes reflect changes in lymphoid compartments clearly involved in HIV related disease like the intestinal mucosa. This study analysed lymphocytes isolated simultaneously from the peripheral blood and duodenal biopsy specimens by three colour flow cytometry in eight asymptomatic HIV infected patients, 26 AIDS patients, and 23 controls. The proportion of CD4, CD8, CD4-CD8-, or gamma delta T cells did not correlate between circulating and duodenal T cells. CD4 T cells were reduced in the peripheral blood (7.5% (25th-75th percentile, 2-16%) v 52% (41-63%), p < 0.0005) and even more reduced in the duodenum (1% (1-2%) v 36% (23-57%), p < 0.0005) of AIDS patients compared with controls. Patients with asymptomatic HIV infection had intermediate CD4 T cells in the peripheral blood (24% (22-35%); p < 0.002 v controls; p < 0.01 v AIDS) but like AIDS patients very low CD4 T cells in the duodenum (3% (1-6%); p < 0.002 v controls). The ratio of duodenal to circulating CD4+ T cells was significantly reduced to 0.2 (0-1) in AIDS patients (p < 0.001) and even to 0.1 (0.04-0.5) in asymptomatic HIV infected patients (p < 0.002) compared with 0.72 (0.44-0.95) in controls. These findings show an early and preferential loss of duodenal CD4 T cells in HIV infection. Immunological abnormalities in HIV infection are distinct between lymphoid compartments, and profound immunodeficiency may occur in the intestinal immune system although circulating T cells are largely preserved.